2021
DOI: 10.1007/s00198-021-05991-7
|View full text |Cite
|
Sign up to set email alerts
|

Fracture-induced pain-like behaviours in a femoral fracture mouse model

Abstract: Summary This study is the first comprehensive characterisation of the pain phenotype after fracture using both evoked and naturalistic behaviours in adult male and ovariectomised female mice. It also shows that an anti-nerve growth factor (NGF) therapy could be considered to reduce pain after fracture surgery. Introduction Bone fractures are common due to the ageing population and very painful even after healing. The phenotype of this pain is still poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…reported mechanical hyperalgesia and cold sensitivity in male mice after sham surgery (no external fixator and osteotomy) and femur fracture over 6 weeks while the sham group significantly improved after 3 weeks (Magnusdottir et al, 2021). This indicates that the wound healing itself already plays an important role in potential pain sensitization after osteotomy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…reported mechanical hyperalgesia and cold sensitivity in male mice after sham surgery (no external fixator and osteotomy) and femur fracture over 6 weeks while the sham group significantly improved after 3 weeks (Magnusdottir et al, 2021). This indicates that the wound healing itself already plays an important role in potential pain sensitization after osteotomy.…”
Section: Discussionmentioning
confidence: 95%
“…Due to the functional impairment, limping as well as changes in gait parameters after osteotomy are expected as a mixture of residual pain due to local inflammatory processes and periosteal pain as well as the restricted functionality of the femur. Magnusdottir et al reported mechanical hyperalgesia and cold sensitivity in male mice after sham surgery (no external fixator and osteotomy) and femur fracture over 6 weeks while the sham group significantly improved after 3 weeks (Magnusdottir et al, 2021). This indicates that the wound healing itself already plays an important role in potential pain sensitization after osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“… 45 This model was recently used to study pain behaviours after fracture. 46 In this model, the pain-like phenotype was maintained 6 weeks after fracture surgery.…”
Section: Animal Models Mostly Used To Study Fracture Painmentioning
confidence: 99%
“…On the basis of the fracture model, the osteoporotic fracture model was developed to study another common fracture in clinical practice, the osteoporotic fracture [ 17 ]. This model is mostly made in female mice (because osteoporosis is more common in postmenopausal women).…”
Section: Cfp Preclinical Animal Modelmentioning
confidence: 99%